Structure‐Guided Evolution of Aryl Alcohol Oxidase from Pleurotus eryngii for the Selective Oxidation of Secondary Benzyl Alcohols. Issue 11 (4th April 2019) - Viña‐Gonzalez, Javier; Jimenez‐Lalana, Diego; Sancho, Ferran; Serrano, Ana; Martinez, Angel T.; Guallar, Victor; Alcalde, Miguel
Abstract: Aryl alcohol oxidase (AAO) is a fungal flavoenzyme capable of oxidizing aromatic primary alcohols into their correspondent aldehydes through a stereoselective hydride abstraction. Unfortunately, this enzyme does not act on secondary benzyl alcohols in racemic mixtures due to the strict control of substrate diffusion and positioning at the active site restricted to primary benzyl alcohols. Here we describe the engineering of AAO from Pleurotus eryngii to oxidize chiral benzyl alcohols with high enantioselectivity. The secondary benzyl alcohol oxidase was remodeled at the active site through four cycles of structure‐guided evolution, including a final step of in vivo site‐directed recombination to address the positive epistatic interactions between mutations. The final variant, with five substitutions and a renovated active site, was characterized at biochemical and computational level. The mutational sculpting helped position the bulkier (S)‐1‐( p ‐methoxyphenyl)‐ethanol, improving the mutant's catalytic efficiency by three orders of magnitude relative to the native enzyme while showing a high enantioselectivity (ee >99%). As a promising candidate for racemic resolution, this evolved secondary benzyl alcohol oxidase maintained its natural stereoselective mechanism while displaying activity on several secondary benzyl alcohols. Abstract :